Tecnicas vivenciales de hábitos e higiene y el desarrollo cognitivo de los niños - niñas del jardín María Tapia de Velasco” de la parroquia urbana de Guanujo, cantón Guaranda, provincia Bolívar, periodo 2010-2011 - Cevallos Fierro, Lourdes Jimena (2011)
The research topic of experiential techniques and hygiene habits and cognitive development of children's garden girls "Maria Tapia de Velasco", the Urban Parish Guanujo, Guaranda Canton, Bolivar Province, the period 2011-2012, raised the question How the Experiential Techniques and Hygiene Habits, bring on the cognitive development of children - girls in the Garden "Maria Tapia de Velasco", the Urban Parish Guanujo, Guaranda Canton, Bolivar Province 2011-2012 period?, which tends to achieve , the overall objective planning Experiential Techniques and Hygiene Habits to the contribution of cognitive development of children, girls, based on the hypothesis with the implementation of Technical and Hygiene Habits Experiential improves cognitive development of children-girls. The data collection was applied direct observation and participant through it became a diagnostic application of hygiene habit and cognitive development. The main conclusions drawn from the children do not pay attention to hygiene habits, and whether their hands are clean dirt or if they got the same, simply because they live in rural communities in this parish, and that parents do not apply in their homes, Technology and Health Habits Experiential certifies that this was a misunderstanding and neglect on the part of children through observation, they managed to raise awareness of the importance of hygiene and that these should be practiced at all where you are, for the good of their health. The children, girls feel the need Experiential Techniques and Hygiene Habits both in the Garden, and at home, for all we can conclude scored the hypothesis was right in this context and Experiential Techniques applied to solve the observation in most of the problems detected in the Garden, how is Experiential Techniques Experiential Techniques The main change is made to define a methodological guide Experiential Techniques and Health Habits. In conclusion, a positive result was obtained with the kids-Girls of the Garden, as it met the objectives proposed in the research.